Stettin Revised: Redating a Major Medieval Inquisition of Heresy - Välimäki, Reima (United Kingdom, 2025)
The article presents a revised dating of a major late medieval inquisition of heresy, challenging the dating of the records established since the 1880s. The inquisitor Petrus Zwicker’s proceedings against Brandenburgian and Pomeranian Waldensians in Stettin did not take place between November 1392 and March 1394, with an 11-month pause between March 1393 and February 1394, as has been the scholarly consensus up till now. Instead, the prosecution was a continuous process that started in November 1393 and lasted till late March 1394. The article discusses the problems of the established dating that is based on now-outdated information about the inquisitor’s itinerary and an ambiguous 15th-century commentary on the register volume. The internal evidence of the register, such as the way different deponents refer to the same events, strongly points towards an uninterrupted process. The revised timeline for the inquisitions solves several contradictions in interpreting the records and proposes new lines of inquiry. A novel reconstruction of the last Waldensian minister’s visit to Stettin and surroundings is provided in the last section of the article. In general, the article addresses the constant need to re-evaluate established interpretations of premodern sources, including those uncontested in the scholarship.